Railway Network, Industrialization, and Development of Langsa, Aceh in 1907”1943 - Rahman, Aulia; Arie Wibowo , Guntur; Akob , Bachtiar (Universitas Airlangga, 2023)
This study aims to reveal the railway networks, industrialization, and development of Langsa, Aceh in 1907-1943s. In the early 1900s, Langsa was designed as a Government Center and a new economic center on the East Coast of Aceh. However, Langsa was not yet connected to the railway networks, so it was necessary to build a railway line as one of the supporting infrastructures. The construction of the railway networks changed many things, ranging from urban landscape, economy, politics, to socio-culture. To pursue the aim of this study, historical methods consisted of heuristics, source criticism, interpretation and historiography were applied. The sources used were colonial archives, contemporary newspapers, contemporary magazines, and other relevant sources. This study found that the construction of the railway networks in Langsa was part of the Dutch colonial government's strategy to maximize economic benefits in the eastern coastal region of Aceh by building connectivity from the North and South regions. The development of the railway networks also had an impact on the growth of the economy, the mobilization of a dynamic population, the growth of good infrastructure for travelers, facilitating communication networks, to encourage the emergence of various types of new professions. However, the construction of the railway networks played a role in environmental damage in the eastern coastal region of Aceh as well as gave insignificant impact on the development of Aceh's indigenous human resources.